Feasibility of Mindfulness for Burn Survivors and Parents of Children with Burns - Eleni Papamikrouli; Marianne B. Kool; Carine van Schie; Nancy E. E. Van Loey (MDPI AG, 2023)
Burn survivors, spouses, and parents of children with burns may experience psychological distress for a prolonged period. Mindfulness-Based Stress Reduction (MBSR) is an intervention that can improve psychological well-being. This study aimed to examine the effectiveness of an MBSR group intervention in a convenience sample. An MBSR group intervention was conducted for burn survivors (n = 8) and parents of children with burns (n = 9), each comprising eight sessions. The participants completed the Beck Depression Inventory-II-NL, PTSS Checklist DSM-5, Five Facet Mindfulness Questionnaire-Short Form, Self-Compassion Scale-Short form, and evaluation questions at baseline, immediately after, and three months post-intervention. All participants completed the intervention. The intervention was rated very useful (M = 8.8), and the participants were very satisfied (M = 8.8). The highest effect was observed in the parents' group on mindfulness skills and self-compassion. For both groups, there was an increase in personal goal scores immediately after the intervention. Qualitative data show that the participants in both groups experienced more inner peace, more awareness of thoughts and emotions, and more self-compassion. This exploratory study suggests that a mindfulness intervention is feasible and can be effective in improving mindfulness skills and self-compassion, particularly in parents of children with burns.